Approbation of a Methodology for Determining the Readiness of a University to Conduct a Professional (Demonstration) Exam for Graduates of Training Programs for Educational Psychologists - Safronova, M.A.; Lisitsyna, A.A. (Psihologo-pedagogičeskie issledovaniâ, 2024)
The article describes a methodology for determining the readiness of a university to conduct a professional (demonstration) exam for graduates of training programs for educational psychologists. The methodology includes collecting the opinions of different subjects of the site for conducting a professional (demonstration) exam at pedagogical universities: the head of the site, heads of departments, undergraduate students (future educational psychologists). The questionnaires contain two sets of questions: the conditions for practical training of educational psychologists, the readiness of pedagogical universities to introduce a professional (demonstration) exam for graduates of educational psychologists. The results of testing the methodology at MSUPE were presented, in which the following participants took part: the head of the site, three heads of departments, 61 fourth-year undergraduate students of full-time study in the direction of 44.03.02 Psychological and Pedagogical Education. The results obtained allow us to say that the university has created organizational, methodological, personnel and material and technical conditions for organizing and conducting a professional (demonstration) exam for undergraduate students. Students mastered each studied area of ​​activity (labor function) of an educational psychologist, both separately in the elements of a professionally oriented module (disciplines, practice) and in the module as a whole. Students have experience passing such an exam in the form of an intermediate certification before the state exam. В статье описана методика определения готовности университета к проведению профессионального (демонстрационного) экзамена для выпускников программ подготовки педагогов-психологов системы образования. Методика включает сбор мнений разных субъектов деятельности площадки для проведения профессионального (демонстрационного) экзамена в педагогических университетах: руководителя площадки, заведующих выпускающими кафедрами, студентов бакалавриата (будущих педагогов-психологов). Анкеты содержат два блока вопросов: условия практической подготовки педагогов-психологов системы образования, готовность педагогических университетов к введению профессионального (демонстрационного) экзамена для выпускников педагогов-психологов. Представлены результаты апробации методики в МГППУ, в которой приняли участие: руководитель площадки, три заведующих выпускающими кафедрами, 61 студент бакалавриата четвертого курса очной формы обучения по направлению подготовки 44.03.02 Психолого-педагогическое образование. Полученные результаты позволяют говорить о том, что в университете созданы организационно-методические, кадровые и материально-технические условия организации и проведения профессионального (демонстрационного) экзамена для выпускников бакалавриата, будущих педагогов-психологов. Студенты освоили каждое изученное направление деятельности (трудовую функцию) педагога-психолога как отдельно по элементам профессионально ориентированного модуля (дисциплины, практика), так и в целом по модулю, имеют опыт сдачи промежуточной аттестации в форме профессионального (демонстрационного) экзамена.